COMPARATIVE OSTEOLOGY OF THE FISHES OF THE FAMILY LEIOGNATHIDAE PART II: RELATIONSHIPS AMONG THE GENERA AND THE SPECIES - James, P S B R (Indian Journal of Fisheries, 2011)
While the three genera, Leiognathus, Secutor and Gazza, in the familyLeiognathidae share some osteological characters in common, they differ fromone another strikingly in certain characters (Table 2). The differences betweenthe genera appear to be more pronounced in the otic region of the skull thanelsewhere.The differences between Leiognathus and Secutor, between Leiognathusand Gazza and between Secutor and Gazza are shown in Tables 3 to 5 respectively.The study indicates that osteologically the genus Leiognathus is moredistantly related to Secutor than Leiognathus to Gazza or Secutor to Gazza